2014
DOI: 10.4103/2141-9248.141971
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status among 12- and 15-year-old children from government and private schools in Hyderabad, Andhra Pradesh, India

Abstract: Background:The assessment of oral health status of children in government and private schools provide data on the oral health status of children from different socio-economic background.Aim:The aim of the following study is to assess and to compare the oral hygiene status, gingival status and caries experience between children from government and private schools in Andhra Pradesh, India.Subjects and Methods:A combination of cluster and stratified random sampling was employed to select the study participants. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
5
12
0
4
Order By: Relevance
“…Using the CPI to assess gingival bleeding in this study, because it is easy to interpret and comparatively reliable, 24 a very high prevalence of gingival bleeding of 92.4% was found in the study population. This is in accordance with a study conducted in the Telangana state of India, where every child had gingival bleeding 25 . Data from a previous study by the authors, conducted in a North Indian child population, also observed a similar prevalence 26…”
Section: Discussionsupporting
confidence: 91%
“…Using the CPI to assess gingival bleeding in this study, because it is easy to interpret and comparatively reliable, 24 a very high prevalence of gingival bleeding of 92.4% was found in the study population. This is in accordance with a study conducted in the Telangana state of India, where every child had gingival bleeding 25 . Data from a previous study by the authors, conducted in a North Indian child population, also observed a similar prevalence 26…”
Section: Discussionsupporting
confidence: 91%
“…Children from rural areas reported higher percentage of inadequate oral hygiene than children from urban areas [19]. Similar results were also demonstrated in public schools when compared to private schools [27] and in lower socio-economic background when compared to a higher socio- economic background [26]. As all the surveyed students were from public schools and almost of similar socio- economic background this factor was not investigated in our survey.…”
Section: Discussionsupporting
confidence: 64%
“…18 Several researches have revealed that oral health of private schoolchildren is better than public school and rural school because of following reasons: private schoolchildren belong to higher socioeconomic status; have more affordability; parent's attitude; dental awareness, and better social support. 15,19 Similar to this study, another research showed a statistically significant difference in decayed, missing, and filled teeth (DMFT) scores between the private and government school children. 16 The prevalence of dental caries among 12-year-old children from private schools and government schools was 32.8 and 70.3% respectively.…”
Section: Discussionsupporting
confidence: 66%